STUDI ANALISIS KOMPARATIF METODE MUTAKALLIMÎN DAN AHNÂF DALAM MENYELESAIKAN PERTENTANGAN DALIL HUKUM - Abdul Jalil (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2017)
Study of methodology istinbâth of Islamic law, good flow of madhhab Ushul Fiqh and expert of Islamic law termed with ta'ârud al-adillah, ta'âdul al-adillah and taqâbul al-adillah. In addressing ta'ârud al-adillah, the flow of Mutakallimîn and Ahnâf takes unequal steps and methods; First, the stages and methods pursued by Mutakallimîn's flow in resolving the first prefix, al-jam'û wa al-taufîq; Second, al-tarjîh; Third, al-naskh and the last with tasâqut al-dalîlain. While the Ahnâf flow, stages and methods of settling the contradictory propositions use steps; First, al-naskh; Second, al-tarjîh; Third al-jam'u wa al-taufîq and fourth, tasâqut al-dalîlain. Secondly, the similarity of the Mutakallimîn and Ahnâf flows when encountering the arguments of the theorem, both of which use the same method, which is different at the stage of step or stage they are used. Stages and methods adopted by the first Mutakallimin flow of al-jam'u wa al-taufîq, while the first stage and method of Ahnâf flow of the naskh. The flow of Mutakallimîn takes precedence over al-jam'u wa al-taufîq rather than doing tarjîh, while the Ahnâf tarjîh school takes precedence rather than compromise the proposition or al-jam'u wa al-taufîq.